A family of octamer-specific proteins present during mouse embryogenesis: evidence for germline-specific expression of an Oct factor. - Schöler, H R (1989)
We have analysed various adult organs and different developmental stages of mouse embryos for the presence of octamer-binding proteins. A variety of new octamer-binding proteins were identified in addition to the previously described Oct1 and Oct2. Oct1 is ubiquitously present in murine tissues, in agreement with cell culture data. Although Oct2 has been described as a B-cell-specific protein, similar complexes were also found with extracts from brain, kidney, embryo and sperm. In embryo and brain at least two other proteins, Oct3 and Oct7, are present. A new microextraction procedure allowed the detection of two maternally expressed octamer-binding proteins, Oct4 and Oct5. Both proteins are present in unfertilized oocytes and embryonic stem cells, the latter containing an additional protein, Oct6. Whereas Oct4 was not found in sperm or testis, it is expressed in male and female primordial germ cells. Therefore Oct4 expression is specific for the female germline at later stages of germ cell development. Our results indicate that a family of octamer-binding proteins is present during mouse development and is differentially expressed during early embryogenesis. Protease clipping experiments of Oct4 and Oct1 suggest that both proteins contain similar DNA-binding domains.